If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v = -2 + 2v Solving v = -2 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. v + -2v = -2 + 2v + -2v Combine like terms: v + -2v = -1v -1v = -2 + 2v + -2v Combine like terms: 2v + -2v = 0 -1v = -2 + 0 -1v = -2 Divide each side by '-1'. v = 2 Simplifying v = 2
| 3(4y+4)=7-5y | | 4=n+4/4 | | -8+7w=9w | | 4=2(x-4)+3-5x | | -12+3y=36 | | -8-4x=-3(x+3) | | -4(x-5)=3-4x | | -8+2g=g | | 6(a+1)=8[a-(3-a)] | | w-14=15 | | 10-2x=100 | | 7(3+n)=28 | | x*x+11x=12 | | -10=-10+5m | | d=6+2d | | 375=45+60h | | 5=3(x-1)+3-2x | | 40+20j=500 | | 3.5-0.04x=1.66 | | 12/k=4 | | 32=-7u+3(u+8) | | 5=3(x-2)+5-4x | | 2x^3-4x^2-30=0 | | 3y-2x=100 | | -120=6(4+6n) | | y=x^4+4x^3+16x | | -12+t=5 | | 3x-55=2x | | 5(1-2a)=-6a+25 | | y=x^4-4x^3+16x | | (3n-8)(-2)=-24 | | 3c-10=2 |